Supply Chain Finance Solutions Relevance - Propositions - Market Value - Hofmann, Erik.; Belin, Oliver; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
The book "Supply Chain Finance Solutions" offers orientation in the new discipline of Supply Chain Finance (SCF) by investigating the need for and nature of SCF, along with its characteristics and enablers. Due to the novelty of the Supply Chain Finance approach, there are still many knowledge gaps. This lack of research leads to uncertainties about the successful implementation of SCF solutions within companies as there is little quantified evidence on the achievable cost savings and other potential benefits. The authors close this gap by providing the latest information on business concepts and the SCF market. Based on a sample SCF model, the worldwide market size for such solutions and potential cost savings to companies engaged in SCF are analyzed. The work underlines the generally agreed-upon attractiveness and future relevance of SCF solutions by creating win-win situations; for all actors in the end-to-end supply chain as well as for external service providers.
Introduction -- Relevance of WCM and its weaknesses -- Characteristics of SCF -- Segmentation of SCF solutions -- Value proposition of SCF -- The market size for SCF solutions -- Concluding remarks -- Annex: OECD ? non-OECD exports per country in 2006 -- OECD ? non-OECD imports per country in 2006 -- Invoice processed and value per industry 2006.-(Aberdeen Group, 2006 -- Days inventory held (DIH) per Industry -- Days Sales Outstanding (DSO) per Industry -- Days Payables Outstanding (DPO) per Industry -- Cash Conversion Cycle (CCC) per Industry -- Literature.
Electronic reproduction.
Keywords: Business logistics; Delivery of goods -- Management; Electronic books